The Influence Of Corporate Social Responsibility, Market Orientation, And Green HRM On Sustainable Business Performance Of E-Commerce Companies - Iwan Henri Kusnadi; Kushariyadi Kushariyadi; Tyahya Whisnu Hendratni; Robby Tanod Mamusung; Afrizal Afrizal; Titis Nistia Sari (Institute of Advanced Knowledge and Science, 2026)
This research intends to investigate the effect of Corporate Social Responsibility, Market Orientation and Green Human Resource Management on Sustainable Business Performance in e-commerce enterprises. The research used the quantitative approach using a survey method, by delivering questionnaires to 220 workers and managers of e-commerce enterprises that were chosen using the purposive sample methodology. Respondents had to be working for at least two years, have been engaged in operational activities and decision-making of the firm and have knowledge of the organization’s policies on sustainability. The data analysis approach was multiple linear regression. Before the analysis, the data were verified for validity, reliability and classical assumption test including normality, heteroscedasticity and multicollinearity. The findings demonstrated that Corporate Social Responsibility, Market Orientation and Green Human Resource Management had good and substantial influence on Sustainable Business Performance partly and concurrently. The study results suggest that sustainable company performance may be improved by enhancing corporate social responsibility, boosting market orientation and adopting human resource management methods for environmental sustainability. The results of this study are intended to contribute to the establishment of sustainability strategies for e-commerce enterprises in the theoretical and practical context.